Report on the Occurrence of Thelyphonus sepiaris (Butler, 1873) (Uropygi:Thelyphonidae) from a Highly Disturbed Iron Ore Mine Site in Sandur Taluk, Bellary District, Karnataka State, India - Pachu, Anish V.; Mohan, V.; Kunhikannan, C.; Kamboj, S. K.; Kumar, Sudhir (Indian Forester, 2019)
No Abstract.